YELLOW PUMPKIN BREAD: PRODUCT ACCEPTANCE ANALYSIS BASED ON SENSORY TESTS AND PHYSICAL CHARACTERIZATION - Yudiastuti , Silvia Oktavia Nur; Halim, Abdul; Rahayuningtyas, Putri Dwi (Sebatik, 2024)
This research seeks to determine the formulation of yellow pumpkin bread. This research used a Completely Randomized Design (CRD) with six different compositions of yellow pumpkin flour, which were 0% (P0), 5% (P1), 10% (P2), 15% (P3), 20% (P4), and 25% (P5). The data obtained was then analyzed using One-way ANOVA and continued with the Duncan Multiple Range Test (DMRT). The research shows that yellow pumpkin flour affects physical properties (specific volume, texture, bread expansion, and bread color intensity) and sensory properties (hedonics and hedonic quality). The chosen formulation of yellow pumpkin bread was P1 (95% wheat flour: 5% pumpkin flour). It has bread expansion at 73.15%, specific volume at 3.46%, texture at 87.44℅, Color (L) at 67.4%, (a) 2.10%, (b) 40.36%, with hedonic quality had a yellowish-white color, tastes somewhat typical of pumpkin, smells somewhat typical of pumpkin, has a soft texture, and the uniform pores.